An Evaluation of the Grover-Counter Test for use in the Assessment of Black South African Township Children with Mental Handicaps - Dickman, Beverley Jo (Department of Psychology, 2015)
The Grover-Counter Test (GCT) is evaluated for use with a group that has been neglected in terms of legislative provisions and services, as well as assessment procedures. Non-handicapped black scholars in racially segregated schools underperformed after the age of 7 years, and this finding is examined in detail. A construct validity study was conducted on a sample of mentally handicapped children using the Griffiths Scales of Mental Development (Griffiths) and the Draw-A-Man (DAM) test. Mental age scores and IQ range scores were used in the correlations with the GCT. The GCT was found to correlate most highly with the expected subscales on the Griffiths; other significant correlations also support the construct validity of the GCT. No difference in performance was found between children with and without language deficits on the GCT; the group with language deficits performed significantly lower on all the Griffiths subscales. Significant correlations were found between the GCT and the DAM. A criterion validity study found that the GCT predicted the level of functioning within the school. Inter-rater reliability and test-retest reliability was high. Detailed discussion is provided of the ethical issues raised by this research. Material from the clinical aspects of the research is presented, as very little documentation of clinical work with this group exists.